Dari Desa Ke Destinasi: Mengembangkan Potensi Wisata Guna Meningkatkan Perekonomian Desa Sambirejo - Ilyasa, Laili Basyarotun; Huda, Syamsul; Utami, Anisa Fitria (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
This research is entitled "From Village to Destination: Developing Tourism Potential to Improve the Economy of Sambirejo Village". The goal is for tourism to become one of the economic drivers, so it is necessary to develop the tourism potential in Sambirejo Village. Based on the problems found in the field, there are still many outsiders who do not know the potential in Sambirejo Village. Therefore, it requires participation from all elements, both the community and the government. The method used in this research is a qualitative research method with a participatory approach. Data collection was carried out by interview, observation and FGD. In the preparation of this service, several steps have been taken including increasing public awareness through the socialization of one home one plant, building a mini garden, building a sign system as a boundary marker between hamlets, training in digitizing MSMEs through digital branding and product photos, and promoting in the form of a QR Code.